Implementation Google Cloud Platform as Data Storage in Industry - Irawan, Achmad Lutfi Helmi (Universitas Syiah Kuala, 2024)
As data volumes grow, the need for cost-effective, scalable and secure data storage solutions is more critical than ever. Google Cloud provides various storage solutions such as Cloud Storage, Bigtable, and Firestore that meet industrial needs. This article explores the application of Google Cloud as a data storage solution in an industry. This research uses a case study approach involving in-depth analysis of one or several sectors implementing Google Cloud as a data storage solution with a survey and experimental approach. Our findings show that implementing Google Cloud as a data storage solution can improve data accessibility, management and analysis, decision-making capabilities, and business outcomes.